Sales Data Management Effectiveness through a Web-Based Information System in Culinary MSMEs - Yesti Siti Nurjanah; Taufik Wibisono; Adinda Nur Indah Sari Sari (Brilliance: Research of Artificial Intelligence, 2026)
Many culinary micro, small, and medium enterprises (MSMEs) still rely on manual sales data management, which often causes reporting delays, recording errors, and limited managerial access to information. This condition is also found at CV. Resto Platina Lestari, where sales transactions and report preparation are not yet supported by an integrated computerized system. This study aims to design and implement a web-based sales information system and evaluate its contribution to improving the effectiveness and efficiency of sales data management compared to the existing manual process. The research adopts an applied system development approach using the System Development Life Cycle (SDLC) with the Waterfall model. Data were collected through observation, semi-structured interviews, and documentation analysis to understand organizational needs and existing workflow limitations. The developed system integrates ordering, transaction processing, payment management, and automated sales reporting within a single platform. The findings indicate that the system improves reporting timeliness, reduces data recording errors, enhances transaction traceability, and provides more structured access to managerial information. The implementation of the web-based system also supports better operational coordination among multiple actors and contributes to more data-driven decision-making processes in culinary MSMEs.